Pérez Serrano, G. (1997). Cómo Educar para la Democracia. Estrategias Educativas. Madrid: Popular. 287 páginas - Fermín Navaridas Nalda (Universidad de La Rioja, 2013)
Pérez Serrano, G. (1997). Cómo Educar para la Democracia. Estrategias Educativas. Madrid: Popular. 287 páginas.